Types and Abundance of Microplastics in Red Snapper (Lutjanus malabaricus) in Kupang Bay Waters, East Nusa Tenggara Timur: Jenis dan Kelimpahan Mikroplastik pada Ikan Kakap Merah (Lutjanus malabaricus) di Perairan Teluk Kupang, Nusa Tenggara Timur - Ngai, Maria Magdalena Mau; Toruan, Lumban Nauli Lumban; Tallo, Ismawan (Habitus Aquatica, 2024)
Microplastics are plastic particles that have a size of